2021
DOI: 10.1039/d1nj02108g
|View full text |Cite
|
Sign up to set email alerts
|

Tolyporphins A–R, unusual tetrapyrrole macrocycles in a cyanobacterium from Micronesia, assessed quantitatively from the culture HT-58-2

Abstract: Tolyporphins A–R are the newest additions to the family of native tetrapyrroles. LC-MS-dMRM and absorption spectroscopy have been employed for analysis of mixtures containing the 18 distinctive natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…The appearance of dioxobacteriochlorin CuBC-3 was observed by absorption spectroscopy when the reaction time was extended to as little as 90 s. The unexpected oxidation of the methylene group flanking the gem-dimethyl group highlights the sensitivity of this site, which has been referred to as the Achilles' heel of the hydroporphyrins [49]. Dioxobacteriochlorins have been prepared previously [50] and are of fundamental interest including as the core chromophore of the naturally occurring macrocycles known as tolyporphins, which are found in a cyanobacterium [51]. The nature of the oxidant underlying the formation of dioxobacteriochlorin in this small-scale reaction (1.0-2.0 mg) is not known.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of dioxobacteriochlorin CuBC-3 was observed by absorption spectroscopy when the reaction time was extended to as little as 90 s. The unexpected oxidation of the methylene group flanking the gem-dimethyl group highlights the sensitivity of this site, which has been referred to as the Achilles' heel of the hydroporphyrins [49]. Dioxobacteriochlorins have been prepared previously [50] and are of fundamental interest including as the core chromophore of the naturally occurring macrocycles known as tolyporphins, which are found in a cyanobacterium [51]. The nature of the oxidant underlying the formation of dioxobacteriochlorin in this small-scale reaction (1.0-2.0 mg) is not known.…”
Section: Resultsmentioning
confidence: 99%
“…4-Carboethoxy-(E)-2-[(4,4-dimethyl-5-methylenedihydrofuran-2(3H)ylidene)methyl]pyrrole (4). Following a reported procedure 20 with some modification, a solution of TiCp 2 Cl 2 (12.0 g, 48.2 mmol) in toluene (125 mL) under an argon atmosphere was treated dropwise with MeLi (67 mL of 1.6 M solution in Et 2 O, 0.11 mol) over 15 min at 0 1C.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
“…3 The chief bacteriochlorophylls are denoted a , b , and g , 1 whereas the tolyporphins include 14 bacteriochlorin members (A–J, L–O). 4 The structures of bacteriochlorophyll a and tolyporphin A are shown in Chart 1. Total syntheses of bacteriochlorophylls and tolyporphins are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the culture (HT-58-2) from Micronesia is the only known producer of tolyporphins. Examination of the culture (16) has revealed that (i) the cyanobacterium is filamentous, (ii) the culture is non-axenic, (iii) community bacteria are attached to the cyanobacterium sheath (17) and (iv) a high level of production of tolyporphins is only achieved under selected growth conditions (18,19). One of the selected growth conditions entails a restricted supply of nitrate in the medium for periods of 5-8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…1(c). Most tolyporphins that contain a dioxobacteriochlorin chromophore exhibit a Q y maximum near 667 nm (18,19), to be compared with chlorophyll a at 666 nm in methanol (661 nm in diethyl ether) (22). Data are not available concerning how various growth conditions might alter the ratio of the various tolyporphins, which could impose an additional uncertainty in the analysis.…”
Section: Introductionmentioning
confidence: 99%